What's worth learning? - Brady, Marion (Emerald Publishing Limited : Information Age Publishing, 2011)
What's Worth Learning? addresses the central question of general education. For learners facing a complex, unpredictable, and dangerous future, it asks and answers the question: What knowledge is absolutely essential for every learner? In simple, jargon-free language, the book explains why the "core curriculum" in near-universal use in America's classrooms was poor when it was adopted in 1893 and why it grows more dysfunctional with each passing year. It then shows how, without changes in staffing, budgets, or bureaucratic boundaries, knowledge can be organized to both radically improve learner intellectual performance and significantly decrease the cost of a general education. Recognizing the difficulty of translating a new idea into classroom instruction, an appendix offers a comprehensive, classroom-tested course of study suitable for adolescents and older students.